2021
DOI: 10.7554/elife.63807
|View full text |Cite
|
Sign up to set email alerts
|

RAL GTPases mediate EGFR-driven intestinal stem cell proliferation and tumourigenesis

Abstract: RAS-like (RAL) GTPases function in Wnt signalling-dependent intestinal stem cell proliferation and regeneration. Whether RAL proteins work as canonical RAS effectors in the intestine, and the mechanisms of how they contribute to tumourigenesis remain unclear. Here, we show that RAL GTPases are necessary and sufficient to activate EGFR/MAPK signalling in the intestine, via induction of EGFR internalisation. Knocking down Drosophila RalA from intestinal stem and progenitor cells leads to increased levels of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 117 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…A previous study showed that RalA expression obviously elevated in CD34+ CML cells [43]. Ral GTPases are responsible for Wnt signaling-mediated intestinal stem cell growth and renewal [44]; this result revealed that RalA might have a close relationship with CML CSCs. RalA also promoted the self-renewal of LSCs.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study showed that RalA expression obviously elevated in CD34+ CML cells [43]. Ral GTPases are responsible for Wnt signaling-mediated intestinal stem cell growth and renewal [44]; this result revealed that RalA might have a close relationship with CML CSCs. RalA also promoted the self-renewal of LSCs.…”
Section: Discussionmentioning
confidence: 78%
“…As reported, the EGF signalling plays important roles primarily in intestinal epithelial cell proliferation and self-renewal, and has a complex interplay with other pathways [33]. Nászai, et al have revealed that RAL GTPases, encoded by RALA and RALB, are necessary and sufficient to activate EGFR signalling and further MAPK signalling in the intestine [34]. Interestingly, we indeed found that the upstream RALA and RALB expression and downstream MAPK expression have great overlap with the local Moran selected spots (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD326 is an epithelial cell adhesion molecule used as a marker for epithelial cells in body fluids ( 26 ). The ectodomain of CD326, EpEX, is a ligand of EGFR, which is highly expressed in the mammalian intestinal epithelium ( 27 , 28 ). EGFR is a key signaling molecule involved in intestinal cell growth, repair, and migration ( 29 ).…”
Section: Discussionmentioning
confidence: 99%